The use of podcast as a challenging didactic material in teaching English as an additional language - CHAGAS, Aryanne Silva das (2024)
This article outlines the results of a research carried out to highlight the instructional utility of podcasts in educational settings and their pedagogical effectiveness in promoting listening comprehension skills in the teaching of English as an additional language. The main objective of this study is to investigate the Podcast's potential for inclusive use, with specific emphasis on improving listening skills, elucidating the associated challenges and restrictions, while articulating the benefits inherent to the integration of podcasts as a robust teaching resource in teaching English language. The methodology consists of a survey research on the use of Podcasts and oral comprehension skills, having 12 University professors as participants. The research approach is qualitative-quantitative, of an exploratory nature, highlighting advantages and disadvantages of the podcast in teaching English as an additional language, including a reflection on the use of the podcast as a future additional language teacher. To achieve these objectives, the article is based on theoretical contributions from authors, such as Tomlinson (1998) and (2000), Nunan (1989), Vilaça (2009), Corrêa et. al (2022), Berto (2022), Silva and Timmermann (2023), Reis, Gomes, Linck (2012) among others. After reviewing the literature, analyzing the data collected from the survey, and the discussion, this research recognizes that the use of Podcasts as teaching materials can promote new experiences in teaching and learning English as an additional language, even if such use still causes some resistance on the part of some teachers.